The Establishment of 3D Polarity-Reversed Organoids From Human Endometrial Tissue as a Model for Infection-Induced Endometritis - Xin Zhang; Li Zhang; Linyuan Fan; Zhaohui Liu (Bio-Protocol)
Endometritis is a prevalent gynecological condition, often resulting from bacterial infections, which poses significant risks to women’s reproductive health, including recurrent pregnancy loss, spontaneous abortion, and intrauterine adhesions. While conventional in vitro models have provided valuable insights into the pathogenesis of bacterial-induced endometritis, they often fail to replicate the complex cellular architecture and microenvironment of the endometrium due to species-specific differences and variations in the menstrual cycle. In this study, we present a novel organoid-based culture system that establishes a bacterial-induced endometritis model using endometrial organoids derived from primary epithelial cells. This protocol involves culturing endometrial organoids in a Matrigel-based three-dimensional matrix, followed by infection with Escherichia coli at a defined multiplicity of infection (MOI). The model effectively recapitulates key pathological features of bacterial-induced endometritis, including disruption of the epithelial barrier, release of inflammatory cytokines, and cellular damage. By preserving epithelial polarity, this approach offers enhanced physiological relevance, improves host–pathogen interaction studies, and provides a robust platform for evaluating potential therapeutic interventions.